2013
DOI: 10.4028/www.scientific.net/ddf.334-335.322
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Influence of Hess-Murray Law on Suspension Flow through Ramified Structures

Abstract: The present study focuses on fluid flow and particle transport in symmetric T-shaped structures formed by tubes with circular and square cross-section. The performances of optimized structures (i.e., structures designed based on constructal allometric laws for minimum flow resistance) and not optimized structures were studied. Flow resistance and particle penetration efficiency were studied both for laminar and turbulent flow regimes, and for micrometer and submicrometer particles. Optimized structures have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is obvious that branching networks are not limited to those with cylindrically shaped tubes and hence they include other flow duct geometries, such as ducts with square cross sectional shape [26], and even free surface open channel networks [21].…”
mentioning
confidence: 99%
“…It is obvious that branching networks are not limited to those with cylindrically shaped tubes and hence they include other flow duct geometries, such as ducts with square cross sectional shape [26], and even free surface open channel networks [21].…”
mentioning
confidence: 99%
“…This is a major simplification, and both experimental [12,20,21,34,45] and numerical [2,13,22,23,24,33,34,40] studies demonstrated that the inherent unsteadiness in blood vessels has a major impact on the exponent of the allometric correlation. c) Independence on the type of fluid Both sap and blood are non-Newtonian fluids, and experimental and numerical studies demonstrate that releasing the newtonianity condition results in a different value of the exponent n in Eq.…”
Section: B) Validity Of the Steady State Flow Conditionsmentioning
confidence: 99%
“…This model is based on counting bifurcations inwards from the periphery. Other approaches, focused on change in size of consecutive vessels generation, are provided by Reis [50], Serrenho and Miguel [51], Miguel [52]. Based on the constructal law, a comprehensive generalized scaling equations are presented for the vessels diameters and lengths of non-symmetric flow structures [51]…”
Section: Laws Of Branched Vessel Network To Fluid Flowmentioning
confidence: 99%